2010
DOI: 10.1007/s00784-010-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal therapy and risk for adverse pregnancy outcomes

Abstract: Periodontitis has been associated with adverse pregnancy outcomes. Results from intervention studies are few and controversial. The present study assessed the effects of non-surgical periodontal treatment in the occurrence of adverse pregnancy outcomes. Two hundred forty-six eligible women were randomly divided into two groups: periodontitis intervention (n = 122; undergoing non-surgical treatment during gestation) and periodontitis control (n = 124; not treated during gestation). Univariate analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 26 publications
2
96
0
5
Order By: Relevance
“…Although all studies described randomization, nine did not adequately describe the random sequence generation methods 3,5,7,12,15,16,17,18,19,20 and nine did not adequately describe allocation concealment 3,5,7,12,15,16,17,18,19,20 . Twelve studies did not use blinding methods for adjudication outcomes 3,5,6,7,12,13,14,15,16,17,18,19,20 . Four trials described a modified intention-to-treat analysis 3,6,13,15 .…”
Section: Characteristics Of Trials Participants and Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although all studies described randomization, nine did not adequately describe the random sequence generation methods 3,5,7,12,15,16,17,18,19,20 and nine did not adequately describe allocation concealment 3,5,7,12,15,16,17,18,19,20 . Twelve studies did not use blinding methods for adjudication outcomes 3,5,6,7,12,13,14,15,16,17,18,19,20 . Four trials described a modified intention-to-treat analysis 3,6,13,15 .…”
Section: Characteristics Of Trials Participants and Interventionsmentioning
confidence: 99%
“…Preterm births < 37 weeks: a meta-analysis of 13 studies 3,5,6,7,12,13,14,15,16,17,18,19,20 showed that periodontal disease treatment during pregnancy had no significant effect on the overall rate of preterm birth (RR = 0.90, 95%CI: 0.68-1.19; p = 0.45; I 2 : 74%) (Figure 2). Low birth weight < 2,500g: a meta-analysis of nine studies 3,5,6,7,12,14,15,17,20 showed a weak association between periodontal disease treatment during pregnancy and decreases in low birth weight, with no significant effect (RR = 0.92, 95%CI: 0.71-1.20; p = 0.55; I 2 : 56%) (Figure 3).…”
Section: Effects Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations